Plak Titreşimlerinin Diferansiyel Kuadratur Yöntemiyle İncelenmesi - Barış, Elanur (Fen Bilimleri Enstitüsü, 2013)
Bu çalışmada sabit kalınlıklı izotropik kiriş ve plakların diferansiyel kuadratur metodu kullanılarak doğal frekansları ve buna karşılık gelen mod şekilleri gibi önemli titreşim karakteristikleri incelenmiştir. Öncelikle plak problemine göre daha basit bir örnek olan kiriş problemi incelenmiş, kirişin çeşitli sınır şartlarında doğal frekansları bulunmuş ve mod şekilleri gösterilmiştir. Daha sonra çeşitli boyutlarda ve çeşitli sınır şartlarında plak titreşimleri hem diferansiyel kuadratur metodu hem de sonlu farklar metodu ile incelenmiş, iki durum için de doğal frekanslar hesaplanmış ve mod şekilleri çizdirilmiştir. Çeşitli parametrelerin değiştirilmesinin plak titreşimlerine olan etkisi incelenmiş ve bu etkiler yorumlanmıştır. Elde edilen sonuçlar her aşamada sonlu farklar metodu sonuçları ve bazı plaklar için literatürde bulunan sonuçlar ile karşılaştırılmıştır. Tüm analizler Matlab Programı kullanılarak yapılmıştır. Elde edilen sonuçların yeterli doğrulukta ve hassasiyette olduğu gözlenmiştir.

In this study, free vibration analysis of isotropic beams and rectangular plates with constant thickness have been achieved using differential quadrature method. In the first analysis section, free vibration analysis of beams which is an easier process than a plate, has been achieved. The natural frequencies and mode shapes have been examined for any combination of the clamped and simply supported conditions. The free vibration of plates has been analyzed using both differential quadrature and finite difference method. The natural frequencies and mode shapes have been examined for any combination of the clamped and simply supported conditions and also for the various ratio of the edges and the number of grid points. The effects of changing various parameters to the natural frequencies and mode shapes have been explained. The obtained differential quadrature results have been compared to mainly finite difference method results, and for some plate configurations have been compared also with the literature results. In all analyses Matlab Program has been used. From the results presented, it can be concluded that differential quadrature method provides the results with adequate accuracy.
Vibration Analysis Of Plates Using Differential Quadrature Method
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2011
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2011
Keywords: Diferansiyel Kuadratur Metodu; Kiriş; Plak; Sonlu Farklar Metodu; Differential Quadrature Method; Beam; Plate; Finite Difference Method